The Influence of Service Quality on Customer Satisfaction in Asik Creative Gresik, East Java - Ardiansyah, Kharisma Eka; Suwaidi, Rahman Amrullah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out how service quality influences customer satisfaction at Asik Creative in Gresik, East Java. This research uses quantitative methods, with the independent variable being service quality and the dependent variable being customer satisfaction. The population in this research are clients who have used the services of Asik Creative. In studies using partial least squares analysis, SEM includes at least 30 to 100 samples. The number of samples taken was 42 respondents. This research uses the SEM PLS method to conduct quantitative analysis. Each indicator is tested for validity and reliability, then continued with the coefficient of determination test, and continued with hypothesis testing using the t-test. The research will produce a statement that service quality has an influence on customer satisfaction at Asik Creative. Based on the results of the analysis and discussion, it can be concluded that product quality has a positive and significant influence on customer satisfaction at Asik Creative Gresik, East Java.